Recruitment System for Educators in Realizing the Quality of Graduates at SMAIT Ihsanul Fikri Mungkid - Imaturrusyda, Imaturrusyda; Usaman, Nurodin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the recruitment system for educators in realizing the quality of graduates at SMAIT Ihsanul Fikri Mungkid. This research method uses descriptive qualitative research methods. The data collection from this research is in-depth interviews, and documentation studies. The results of this study are the implementation of the recruitment of new educators which aims to obtain qualified educators and are able to carry out the institution's vision and mission, to realize quality graduates in academic and non-academic terms. The conclusion of this study is that the recruitment system for educators in realizing the quality of graduates in accordance with the vision and mission of SMAIT Ihsanul Fikri Mungkid is carried out by the SDI Foundation Division, the Principal, the Deputy Principal for the Curriculum Sector with 5 stages , namely job vacancies announcement, file collection and selection, tests writing which includes 4 competencies, microteaching, and a test to read Qur'an. With the recruitment system for new educators implemented by the institution, it is an effort to realize the quality of graduates in accordance with the vision and mission of the institution. This can be seen in general from the achievements achieved from year to year which continue to increase because the recruitment process for new educators from year to year is also being tightened, so that the teaching staff in the institution are also in accordance with the roles carried out until finally achieved vision and mission of the institution with quality graduates